2021
DOI: 10.3390/jcm10235573
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of COVID-19 on Out-Hospital Cardiac Arrest Survival Outcomes: An Updated Systematic Review and Meta-Analysis

Abstract: Cardiopulmonary resuscitation in patients with out-of-hospital cardiac arrest (OHCA) is associated with poor prognosis. Because the COVID-19 pandemic may have impacted mortality and morbidity, both on an individual level and the health care system as a whole, our purpose was to determine rates of OHCA survival since the onset of the SARS-CoV2 pandemic. We conducted a systematic review and meta-analysis to evaluate the influence of COVID-19 on OHCA survival outcomes according to the PRISMA guidelines. We search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
46
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 68 publications
10
46
1
1
Order By: Relevance
“…Our study found rates of survival to hospital admission (OR = 0.56–0.65) and survival to hospital discharge (OR = 0.46–0.68) to be slightly higher than what is reported in the literature [ 13 , 19 , 24 , 25 ]. While the rates of good neurologic scores did not change significantly in our study, conflicting research exists, demonstrating worse or unchanged CPC scores compared to the pre-COVID-19 period [ 12 , 26 ].…”
Section: Discussioncontrasting
confidence: 74%
“…Our study found rates of survival to hospital admission (OR = 0.56–0.65) and survival to hospital discharge (OR = 0.46–0.68) to be slightly higher than what is reported in the literature [ 13 , 19 , 24 , 25 ]. While the rates of good neurologic scores did not change significantly in our study, conflicting research exists, demonstrating worse or unchanged CPC scores compared to the pre-COVID-19 period [ 12 , 26 ].…”
Section: Discussioncontrasting
confidence: 74%
“…Among patients with COVID-19, the incidence of IHCA for non-ICU patients was 2.2% and 15.4% for ICU patients [ 48 ]; cardiac arrest most often occurred on hospital day 4 [ 18 , 26 ]. For IHCA patients with COVID-19 infection, ROSC varied from 13.2–54%, survival to hospital discharge ranges from 0 to 12%, and good neurologic outcomes 0–0.7% [ 14 , 15 , 17 , 44 , [48] , [49] , [50] , [51] ]; when considering inpatient location of cardiac arrest, survival to hospital discharge was worse for non-ICU patients (0.7%) versus ICU patients (9.1%) [ 48 ]. As noted in the OHCA population, co-morbid conditions also occurred with greater frequency among inpatients [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…For IHCA patients with COVID-19 infection, ROSC varied from 13.2–54%, survival to hospital discharge ranges from 0 to 12%, and good neurologic outcomes 0–0.7% [ 14 , 15 , 17 , 44 , [48] , [49] , [50] , [51] ]; when considering inpatient location of cardiac arrest, survival to hospital discharge was worse for non-ICU patients (0.7%) versus ICU patients (9.1%) [ 48 ]. As noted in the OHCA population, co-morbid conditions also occurred with greater frequency among inpatients [ 49 ]. The majority of IHCA patients presented with a non-shockable rhythm (89%) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis was conducted to overcome the limitations of individual investigations, and results with implications for OHCA epidemiological features and mortality, which were notably different from those before to the pandemic, were reported. [1] , [2] , [3] , [4] Several observational studies and meta-analyses found that the composition of OHCA patients changed as the number of cardiac arrests increased in COVID-19 patients, where respiratory failure is a somewhat more prevalent cause. In addition, an increase in home arrest due to the effect of social distancing measures and self-quarantine isolation, as well as an influence on the weakening of the chain of survival due to the concentration of medical resources on COVID-19, were shown as an indirect effect.…”
Section: Introductionmentioning
confidence: 99%
“… 1 The updated meta-analysis included 31 articles and showed no significant differences in the outcomes, demonstrating a similar trend. 4 However, when compared to the unsystematic healthcare system and poor public health services due to partial concentration of medical resources for the treatment of COVID-19 at the beginning of the pandemic, several factors such as a systematically changed medical environment, improved response ability for patient with confirmed or suspected the COVID-19, increased vaccination rate, and change of the main COVID subtype show differences varies with the time and region of COVID-19 spread in recent environment. Therefore, combining the all-time data after the COVID-19 outbreak and comparing it to data before pandemic could lead to serious interpretation errors.…”
Section: Introductionmentioning
confidence: 99%